Assessment of knowledge gap on cigarettes and other tobacco products act (COTPA) among tobacco vendors in Puducherry: A mixed-method study - Lalithambigai Chellamuthu; J Jenifer Florence Mary; T D Subhaashini (Wolters Kluwer Medknow Publications, 2023)
Background: Tobacco usage has been identified as a leading preventable cause of mortality and is responsible for six million fatalities per year globally. India had enacted COTPA in 2003. Tobacco vendors are one of the key stakeholders for Cigarettes and Other Tobacco Products Act (COTPA) implementation. Objective: To assess the knowledge gap on COTPA and to explore the perceived factors influencing implementation of COTPA among tobacco vendors in Puducherry. Materials and Methods: A mixed-method study was conducted among tobacco vendors from Point of Sale (PoS) around 230 educational institutions (schools and degree colleges) in Puducherry for three months. Simple random sampling was applied to select educational institutions and the tobacco vendors from PoS located around these institutions were included. Data capture was done using a pretested, face-validated questionnaire incorporated in Epicollect software 5 and data analysis by SPSSv24. Purposive sampling was employed to conduct in-depth interviews among tobacco vendors till the point of saturation and manual content analysis performed. Written informed consents were sought. Institutional Ethical Committee approval was obtained. Results: Majority (95.7%) reported that they were aware of tobacco control legislation, but only one person had heard of COTPA. Awareness about the display of signage boards at PoS was observed in 75.7% vendors. Around 41.7% reported that they should not advertise any kind of tobacco products. Three major themes were identified: facilitators, barriers, and suggested measures for COTPA implementation. Conclusion: Tobacco vendors in Puducherry were aware of tobacco control legislations but not familiar with the COTPA and its provisions. It is necessary to put forth efforts to educate these important stakeholders to be more cognizant of COTPA and to effectively include them in anti-tobacco programs.